The Confusion - Stephenson, Neal (London William Heinemann, 2004)
It is the late 1600s on the high seas. A group of Barbary galley slaves plot as they ply the oars of a pirate ship. These ten men - unfortunates from around the world impressed into servitude - have heard whispers of an enormous cache of Spanish gold. Together, they hatch a daring scheme - escape their chains, seize a ship, and find the treasure. And, amazingly, they succeed - leaving some very unhappy men behind who vow to hunt down the vagabonds and bring them to justice, no matter the cost. Meanwhile, back in France ... The beautiful Eliza, toast of Versailles and spy extraordinaire, attempts to return to London with her baby, a child whose paternity is shrouded in mystery. As she makes her way home from the Continent, her ship is stopped by a French privateer - and she is returned to the Sun King's court. Thrown back into a web of international intrigue, Eliza must contend with all manner of characters, including buccaneers, poisoners, Jesuits, financial manipulators, and ever the stray cryptographer or two.-In this hugely ambitious, profoundly compelling adventure, Neal Stephenson brings to life a cast of unforgettable characters in a time of breathtaking genius and discover
Keywords: Women spies